If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z/2+9=11
We move all terms to the left:
z/2+9-(11)=0
We add all the numbers together, and all the variables
z/2-2=0
We multiply all the terms by the denominator
z-2*2=0
We add all the numbers together, and all the variables
z-4=0
We move all terms containing z to the left, all other terms to the right
z=4
| 5(t+2)+4(t+1)=-4 | | -2/5=3/4+n | | 4x+11=116 | | 3x^2+x=3 | | 156=12X+2y | | -43=x+14 | | 37=29-8(2-4w) | | 8/15=6/n | | 4a-(-4a-1)=17 | | 2(1.5m+3)=(3.5m-1 | | 2x-3=-25.31 | | x-2.5x+6x-3=(2x-1) | | 3x–1–4x=–2x+7x– | | t+(3t+5)=13 | | 8(2y=+5)=9y+12 | | -6-2(4y+5)=0 | | 7³+5=7¹-x | | n2−9n+18=0 | | A=((30x^2)-4x)/((5x^2)+2x) | | 10v^2+19v+6=0 | | 6-2x=-9x+18 | | s/2=-5 | | (4d-1)(d-9)=0 | | -3(m-2=12 | | 4+4z/3=6 | | X2+5x-234=0 | | 2(5x-3)+2=-2 | | 5(y-3)=38 | | m/5=9/6 | | .25x+106=180 | | m/5=-9/6 | | 21y=38 |